The Effect of Groundsill Height on Bridge Pillar Flow Characteristics (Physical Model) - Raissa, Azarine Vashti Alpha; Priyambodho, Bambang Adhi; Purnaditya, Ngakan Putu; Wigati, Restu; Subekti, Subekti (Jurnal Fondasi, 2023)
Groundsill is one of the categories of wide thresholds that are generally built transversely in the river downstream of a building threatened with damage caused by scouring such as bridge pillars. In addition to construction factors, local scour around the pillars can be another factor causing the collapse of the bridge structure. The purpose of this study was to determine the effect of groundsill height on flow characteristics. Physical model research on open channels (flume) was carried out at the Integrated Laboratory of Sultan Ageng Tirtayasa University, Sindangsari Campus. The groundsill model is modeled with dimensions of 8 cm peak width, 30 cm length, and groundsill height variations (1, 2, 3, 4, and 5 cm) made of wood while the bridge pillar model is modeled with a diameter of 1 inch made of PVC pipe which is filled with concrete. The results showed that the higher the groundsill (p), the higher the water level upstream (H1) is greater and downstream (H2) is smaller, while the flow speed upstream (V1) is smaller and downstream (V2) is greater so that the Froude number downstream is greater than upstream. The higher the groundsill (p), the Froude number downstream will increase (supercritical flow) while upstream will decrease (subcritical flow).